Surgical Treatment of Patients with a Bicuspid Aortic Valve and Concomitant Expansion of the Ascending Aorta - Olena M. Trembovetska; Olha V. Pantas; Vitalii I. Kravchenko; Ivan M. Kravchenko; Iryna A. Osadovska (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To evaluate the rate of long-term complications on ascending aorta after bicuspid aortic valve (BAV) replacement depending on the type of defect (stenosis or insufficiency) and to determine the indications to certain type of surgery in this category of patients.Materials and methods. One hundred five patients underwent BAV replacement between 2007 and 2014. The patients were divided into two groups. Group 1 included 63 patients with stenosis prevalence, group 2 included 42 patients with insufficiency. Aortic diameter at the level of the sinuses of Valsalva and at the level of the ascending aorta was assessed preoperatively and in the long-term postoperative period.Results. Long-term results were studied in 86 (81.9%) patients during 6.8 ± 2.2 years at the average. Sixteen (18.6%) patients developed aortic complications: 6 (6.9%) of them had progressive dilatation (10% from initial diameter), aneurysm formation was detected in 8 cases (9.3%) with 6 cases (6.9%) of dissection, 1 patient (1.3%) had aortic rupture. Freedom from ascending aorta dilatation within 13 years after BAV replacement was 95.1% in group 1 and 62.3% in group 2. Freedom from aortic dissection within 13 years after BAV replacement was 90.1% at the average (97% in group 1 and 80.6% in group 2).Conclusion. The tactics of aortic aneurysm correction in BAV depends on its diameter and, to a lesser extent, on the presence of stenosis or insufficiency of the valve. With existing stenosis and a diameter of the ascending aorta up to 4.5 cm, it is possible to consider correction without intervention on the ascending aorta. The presence of valve insufficiency in such a situation often requires additional manipulations on the ascending aorta.